Penggunaan Model Blended Learning dalam Mata Pelajaran Bahasa Indonesia di Era Normal Baru - Faridah Eriyaningsih; Hariyadi Hariyadi; Agus Nuryatin (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
Life in the New Normal era makes adjustments in education. When the situation was still in a pandemic, learning was carried out fully online, now we had to switch to face-to-face learning, but it is still limited. This study aims to explain the assumption of using a blended learning model implemented using Simpel-12 in the New Normal era. The method used is descriptive with a qualitative approach. Participants in this study were representatives of students at SMAN 12 Semarang who carried out blended learning. The research was carried out in Indonesian class subjects. The results showed that teachers and students agreed that the blended learning model was more effective in teaching. Students' understanding of the material is recognized as better when blended learning is compared to fully online learning.